"NEET" youth: A stigma that blurs the social problems of young people - Juan García-Fuentes; José Saturnino Martínez García (Arizona State University, 2020)
This article is aimed at thinking about NEET (Not in Education, Employment, or Training) youth and at proving experientially that the NEET concept is a way to hide social problems impacting youth because it does not take into account the structural restrictions that lead to this situation. This situation has become a pattern of social imbalance, where the lack of work experience promotes a vulnerable situation for those who just start to enter the labour world, which may leave "scars" in their lives. We present an analysis on youth transitions, where not every youth achieves to get out of job insecurity as an adult. An uncertain market of low wages is unsafe and flexible, and does not address the necessities of youth, who are paralysed in a socioeconomic crisis with few opportunities. This article approaches a selection of bibliographical sources and describes the information collected by the Working Population Survey (WPS) about the evolution of NEET, its relation with the job market, and the reasons why these youth do not look for employment. We conclude by arguing that weak work prospects end up deteriorating the citizen rights of the youth population.